Accelerating Islamic Learning in the Digital Era : Contemporary Strategies for Building a Knowledgeable, Charactered, and Adaptive Generation Amidst Global Transformation - Nur Iffah Qoyyumillah; Huril‘in Huril‘in; Saeful Anam (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The aim of this research is to analyze the development and implementation of contemporary learning methods in the context of Islamic education, highlighting the role of digital transformation in enhancing the effectiveness and relevance of religious education. The approach used is a literature study with a qualitative method, analyzing scientific literature and related credible sources. The main findings indicate that the integration of digital technology such as LMS, interactive videos, and artificial intelligence can enhance student engagement, collaboration, and the development of critical and creative skills, thereby addressing the challenges of the times. However, the limitations of the research include the lack of direct empirical data from field applications and the need for adaptation to local characteristics. The practical implication of this study is the importance of developing teacher competencies and designing a flexible and contextual curriculum to support the effective implementation of this method. The original value of this research lies in the integration of contemporary educational concepts with Islamic educational values, as an innovative solution to meet the needs of adaptive and meaningful education in the global digital era.